Size control synthesis and amperometric sensing activity of Palladium nanoparticles for Glucose detection. (2018) - Mahajan, A.; Banik, S.; Chowdhury, S. Roy; Roy, P.S.; Bhattacharya, S.K.
Abstract: Size controlled synthesis of palladium nanoparticles of varying average diameter ranging from 8.1 to 21.3 nm, was executed by controlling the time of reflux of the facile reduction of PdCl2 in a single pot using citric acid as reducing agent in presence of the steric stabilizer poly vinyl alcohol in water. The as synthesized nanomaterials were analysed by different microscopic techniques and utilized for the construction of a few anode-catalysts for biosensing of glucose. The catalytic activity of the anodes was characterized by cyclic voltammetry and chronoamperometry in different glucose solutions of varying concentration in 0.1M aqueous alkali. The maximum sensitivity is 66.2 µA cm -2 mM -1 found at the potential of 0.1V with respect to HgO/Hg electrode, for the particles having optimum crystallite-diameter of 12nm obtained from the solution having reflux time of 1.5 hour. The lowest limit (8.33 µM) and long linear range of detection (8.33 to 166 µM) are also important parameters of the best sensor studied. The results seem to help a better understanding and improvement of Palladium-based amperometric glucose sensor.